Activating labour market policies and the restructuring of welfare and state: a comparative view on changing forms of governance - Irene Dingeldey (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2009)
Analysis of the change of governance in activating labour market policy in Denmark, the UK and Germany supports the restructuring thesis advanced in the course of the debate on how to classify the change in the welfare state. New objectives, such as 'the promotion of employability', have been accompanied by a general trend towards a decline in state responsibility for service delivery and a reduction of rights to transfer payments. At the same time, however, the state's responsibility as guarantor in respect of rights to social services has increased and the obligation to work has been introduced, in conjunction with an increase in reflexive forms of governance. Thus the observed restructuring has brought about a change in the nature of both welfare and state. Although the outlined trend of changing forms of governance and statehood is to be found in all three countries, level and scope of certain instruments and governance forms vary strongly, and characterise the emergence of quite different activating policies, respectively a convergent divergence of welfare state development.
Keywords: 320